Stres Psikososial dan Kejadian Fluor Albus Patologis pada Santri - Chusnul Hana; Nabila Zuhdy; Hesty Widyasih (Jurnal Forum Kesehatan, 2018)
Fluor albus or vaginal discharge is a secretion from the woman’s genitals but it is not a blood. Fluor albus divided into physiological and pathological fluor albus. Pathological fluor albus is a secretion from vagina that whitish, yellowish or greenish, itching or burning or pain. Fluor albus is not a disease but becoming the indication of infections, viciousness or benign tumor of gynecological problems. There are many factors can caused fluor albus at adolescent, one of the factors is stress. This study aimed to know the correlation between psychosocial stress and incidence of pathological fluor albus of islamic boarding students as research population in Pondok Pesantren Sunan Pandanaran Sleman Yogyakarta. The sampling technic used non-probability sampling and the sample size was 82 people. This study used Depression Anxiety Stress Scale (DASS 42) and fluor albus questionnaires to collect the data. The data analyzed using Chi-Square, Coefficient Contingency and Prevalence Ratio test.Result of the study showed 58,7 % santri had stress and 64,9% santri were indicated pathological fluor albus. At the age of characteristic respondent, the majority subject was the end of adolescent (50,5%) and the majority subject was at higher education (41,2%). Statistical test showed p-value = 0,001, C = 0,523 and PR = 2,982, which means there were significant correlation between level of psychosocial stress and incidence of pathological fluor albus, the correlation strength was strong enough. Santri who got stress psychosocial have risk 2,982 times experienced pathological fluor albus incidence.